An investigation into the novel effects of melatonin treatment on differentiated C2C12 myotubes in the absence and presence of pathology - Wentley, Garth Nicholas (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.